2022
DOI: 10.1017/jfm.2022.168
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear optimal growth mechanisms for generating turbulent bands

Abstract: Recently, many authors have investigated the origin and growth of turbulent bands in shear flows, highlighting the role of streaks and their inflectional instability in the process of band generation and sustainment. Recalling that streaks are created by an optimal transient growth mechanism, and motivated by the observation of a strong increase of the disturbance kinetic energy corresponding to the creation of turbulent bands, we use linear and nonlinear energy optimisations in a tilted domain to unveil the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…The real parts of these autocorrelations also show the same sign reversal near the channel center as the NLOP [46]. In plane Poiseuille flow, the destabilizing velocity autocorrelation instead vanishes near the channel center, which is consistent with both the behavior of the NLOP [47] and results analyzing optimal secondary energy growth [48]. In contrast, linear optimal perturbations of plane Poiseuille flow peak near the channel center; see e.g.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The real parts of these autocorrelations also show the same sign reversal near the channel center as the NLOP [46]. In plane Poiseuille flow, the destabilizing velocity autocorrelation instead vanishes near the channel center, which is consistent with both the behavior of the NLOP [47] and results analyzing optimal secondary energy growth [48]. In contrast, linear optimal perturbations of plane Poiseuille flow peak near the channel center; see e.g.…”
Section: Introductionsupporting
confidence: 80%
“…In contrast, linear optimal perturbations of plane Poiseuille flow peak near the channel center; see e.g. the comparison in [47]. The agreement of these results with those from various nonlinear analysis approaches provides further evidence that behavior associated with nonlinear effects can be captured using SIOA-based approaches.…”
Section: Introductionsupporting
confidence: 58%
“…This asymmetric wavepacket evolves via nucleation of new streaky structures (see Parente et al. (2021) concerning the mechanism of creation of the streaks) in the direction of the inclined laminar–turbulent interface, clearly forming a singular turbulent band, as can be observed for . The newly formed turbulent band continues growing in an oblique direction with angle until reaching the periodic boundaries, where it interacts with itself ().…”
Section: Resultsmentioning
confidence: 88%
“…In order to reduce the computational cost, some numerical studies cleverly considered computational domains tilted in the direction of the bands, as done for plane Couette flow by Barkley & Tuckerman (2005) and for plane Poiseuille flow by Tuckerman et al (2014). Very recently, Parente et al (2021) carried out an optimal growth analysis in a tilted domain with given angle. They showed that although linear optimization is able to recover the main wavenumbers observed by direct numerical simulation, nonlinear effects are necessary for providing large-scale flow and spatial localization of the perturbation able to generate a turbulent band.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation